1984
DOI: 10.1039/an9840901589
|View full text |Cite
|
Sign up to set email alerts
|

Determination of arsenic, antimony, bismuth, cadmium, copper, lead, molybdenum, silver and zinc in geological materials by atomic-absorption spectrometry

Abstract: Arsenic, antimony, bismuth, cadmium, copper, lead, molybdenum, silver and zinc are very-useful elements in geochemical exploration. In the proposed method, geological samples are fused with potassium pyrosulphate and the fusate is dissolved in a solution of hydrochloric acid, ascorbic acid and potassium iodide. When this solution is shaken with a 1O0/o VNAliquat 336isobutyl methyl ketone organic phase, the nine elements of interest are selectively partitioned in the organic phase. All nine elements can then be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Zongshou Yu et al (4) reported different digestion techniques such as HF/HClO 4 , HF/HNO 3 , and HF/H 2 SO 4 to dissolve geological samples for trace element determination. Silver and cadmium were also estimated in geological samples with the help of FAAS and GFAAS by several authors using different acid and fusion mixtures (3,(5)(6)(7)(8). There are some complete dissolution and some partial decomposition techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Zongshou Yu et al (4) reported different digestion techniques such as HF/HClO 4 , HF/HNO 3 , and HF/H 2 SO 4 to dissolve geological samples for trace element determination. Silver and cadmium were also estimated in geological samples with the help of FAAS and GFAAS by several authors using different acid and fusion mixtures (3,(5)(6)(7)(8). There are some complete dissolution and some partial decomposition techniques.…”
Section: Introductionmentioning
confidence: 99%
“…an inductively coupled plasma (AES-ICP) [1][2][3][4][5], or after the separation and concentration of the elements of interest [6][7][8][9][10][11][12]. Radioanalytical instrumental methods (instrumental neutron activation analysis -INAA, X-ray fluorescence spectrometry -XRF, and particle (proton) induced X-ray emission -PIXE) are rarely used to determine trace elements in these matrices due to matrix and inter-element interferences and background effects [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been carried out concerning the determination of trace elements in iron ore materials directly from the dissolved samples by atomic absorption spectrometry (AAS) and atomic emission spectrometry with an inductively coupled plasma (AES-ICP) [1][2][3][4][5][6][7], or after the separation and concentration of the elements of interest [8][9][10][11][12][13][14][15]. Instrumental methods (instrumental neutron activation analysis -INAA, X-ray fluorescence spectrometry -XRF, and particle (proton) induced X-ray emission -PIXE) are also *Author for correspondence (E-mail: radojko.jacimovic@ijs.si).…”
Section: Introductionmentioning
confidence: 99%